Molecular and Cytoskeletal Changes in Breast Cancer Cell Lines Treated With Newcastle Disease Virus Strain Af2240 - Eshak, Zolkapli (2006)
The study was carried out to investigate the oncolytic effect of Newcastle disease virus (NDV) strain AF2240 on the MCF-7, MDA-MB-231 breast cancer cell lines and 3T3 fibroblast. Studies were conducted to investigate the cytoskeletal protein structure and the molecular changes of the oncogenes. The AF2240 strain of NDV was propagated in 11 days old embryonated eggs for 72 hours. The virus in the allantoic fluid was harvested, purified and stored at -80ºC. The haemagglutination (HA) test was conducted on the purified virus to determine the HA titre of the NDV strain AF2240 which was 16384 HA units. The inhibition concentration of AF2240 towards several types of breast cancer cell lines was carried out using microculture tetrazolium (MTT) assay via two methods; monolayer and co-culture techniques to determine the inhibition concentration (IC50) value. The IC50 values for MDA-MB-231 breast cancer cell lines treated with NDV strain AF2240 were 8 and 2 HA units for the monolayer and co-culture techniques respectively, whereas the IC50 value for MCF-7 was 2 HA units for both techniques. NDV strain AF2240 has no oncolytic effect towards 3T3 mouse fibroblast. Further on confocal microscopy was carried out to observe the localization of the virus in the cells. For detection of the virus, polyclonal antibody and anti-chicken conjugated with fluorescein isothiocynate (FITC) were used. The virus particles were detected in the cytoplasm of both breast cancer cell lines after 24 and 48 hours post treatment. Budding-off of the virus was detected after 72 hours post treatment. Further study using TdT- mediated dUTP nick-end labelling (TUNEL) assay was conducted to label and quantify the percentage of apoptotic cells. By using independent t-test, the analysis revealed that NDV strain AF2240 works better towards MDA-MB-231 cells compared to MCF-7 (p ≤ 0.05). These methods confirmed that NDV causes cell death to the breast cancer cells via apoptosis. The finding also suggesting that NDV react better towards MDA-MB-231 cells compared to MCF-7 cell (P≤0.05). The immunolabelling of the cytoskeletal proteins, namely, microfilaments, microtubules and intermediate filaments was conducted by using FL Phallicidin, monoclonal anti-α-tubulin FITC and monoclonal anti-vimentin Cy3. The cytoskeletal proteins of the cell lines were disrupted after 72 hours post treatment. However, the number of cells with disrupted cytoskeletal proteins was much higher in MDA-MB-231 cells compared to MCF-7 cells. The study of oncogenes was conducted by using reverse transcriptase polymerase chain reaction (RT-PCR) method. The expressions of c-myc, c-erb-2 and c-fos oncogenes were detected at pre and post-treatment in the MCF-7 and MDA-MB-231 breast cancer cell lines. These results prove that cells which had undergone apoptosis due to NDV strain AF2240 treatment did not suppress the oncogenes. This study concluded that even though strain AF2240 of NDV have significant cytotoxic effect towards MCF-7 breast cancer cell lines, the number of apoptotic cells were higher in MDA-MB-231 cell line and therefore, further study is needed to understand the underlying mechanism in making the NDV strain of AF2240 as an anti-cancer agent.